ICT complement for supporting flute study at home. (28th November 2022) - Bravo, Paloma; González, Iván; Bravo, José
Many countries propose flute studies in primary school. Usually, students have only one class per week, which makes it inconvenient for teachers to pay attention to students individually. Another problem is that, after lessons, students have to practice alone at home. Thus, the responsibility for progress lies almost entirely with the learner. This paper proposes a digital tool as a complement to alleviate both problems. The app provides a listening tool, music scores view, records learner performances and offers feedback about students' mistakes during their performances. Finally, the student evolution is sent to the teacher in an adequate manner, to achieve more effective teaching in each class.